Bilangan Kromatik Graf Hasil Operasi Korona Sisi Graf Siklus dan Graf Bintang - Alivia Alivia; Kartika Yulianti; Yaya S. Kusumah (Jurnal Matematika, Statistika dan Komputasi, 2025)
One of the concepts in graph theory that can be analyzed is chromatic numbers of a graph and operation of two graphs. There are various kinds of operations of two graphs, one of which is the corona edge operation. This research aims to determine the chromatic number of the edge corona operation of graph Cn*K1,m  and K1,m*Cn, where Cn is a cycle graph and K1,m is a star graph. The chromatic number is determined based on the pattern formed from several n and m values. The results of this research show that the chromatic number of the edge corona operation of graph Cn*K1,m  is 4 for n= 3, 4, ... k   and m=1, 2, 3, ..., l. The chromatic number of the edge corona operation of graph K1,m*Cn is 5 if n is odd number. and is 4 if n is even number.